Inclusion levels of flour made from smoked Nile tilapia trimmings in extruded corn snacks (Research, Society and Development, 2021)
This study aimed to elaborate extruded corn snacks with the inclusion of flour made from smoked Nile tilapia trimmings, as well as evaluate the chemical, sensory and microbiological composition. The tilapia trimmings flour was incorporated in four levels, one of them was the control (without inclusion) and then 5%, 10% and 15% added in the corn grits. The microbiological analysis shows that the flours and snacks prepared are within the microbiological standards. The shavings flour presented 8.89% moisture, 60.87% protein, 15.7% ash and 11.68% carbohydrates. The inclusion of different levels of tilapia flour in the extruded snacks significantly influenced only the content of protein, moisture and carbohydrates. The protein content increased as the level of inclusion of shavings in the snacks increased, while the carbohydrate content decreased. For protein, there was a positive linear effect, whose contents went from 7.06% to 11.44%. Carbohydrate had a negative linear effect, reducing from 78.20% to 72. 63%. The moisture content showed a quadratic effect, with a range from 5.26 to 6.03%.  As for sensory analysis, there was no significant difference for any of the attributes evaluated between the different treatments. It is recommended to include up to 15% of Nile tilapia trimmings flour in extruded corn snacks with an increase in protein content of up to 38.29% and a reduction of up to 7.12% in carbohydrates.